Peningkatan Kinerja Kepala Sekolah dengan Mengefektifkan Kelompok Kerja Kepala Sekolah melalui Supervisi Akademis Pengawas - Wahidin (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2021)
Principal performance is not only based on formal education but must also be based on the ability of prinscipals in performing roles and functions in schools effectively and in terms of academic principals are also required to be able to, encourage, choose and use methods, media and help Because that, learning as relaxed as the principal not only as a school manager but also as a teacher / teacher in the classroom. To support success in the changes made and expected, professional school principals need to be prepared, who are willing and able to plan, implement and evaluate various policies and changes made. The purpose of this study is to learn how to improve supervisory managerial supervision in improving the performance of school principals by making the school principal workgroup (KKKS) effective in the SD Binaan District of Sekongkang District. In this action research carried out in 3 cycles, the results of the actions taken proved to be able to improve the performance of school principals by achieving ideal standards. From 58.75% in Cycle 1, it could increase to 68.89% in Cycle II, and cycle III increased to 80.56%. The results of this action research show that supervisors' supervision through Managerial supervision of supervisors is effective in increasing the performance of school principals in the Elementary School Assisted I Group of Unter Iwes with 100% achievement